PERAN PEREMPUAN PADA RITUAL KENELAYANAN DAN PERBEKALAN MENCARI IKAN - Andy Ahmad Zaelany (Research Centre for Population, Indonesian Institute of Sciences, 2010)
Traditional role of women in the fishing community of Barrang Lompo island focuses on ritual religious activity before fishermen fishing and selling fishing supplies. Until now the development of governments programs, such as sea conservation and introduction of new fishing technology, are gender bias, and tend to fail in the end of the programs. Understanding of women s cultural space is then very important to accelerate the implementation of the development program for the fishermen community.